Address Terms in Emily In Paris Season 1 Episode 1: A Conversation Analysis - Kadek Intan Adinda Lesmana (International Journal of English and Applied Linguistics (IJEAL), 2022)
This study entitled "Address Terms In Emily In Paris Season 1 Episode 1: A Conversation Analysis" was restricted to the sociolinguistics area regarding address terms. This study aimed to analyze the type of address terms and the social factors that influence the use of address terms by the characters in "Emily in Paris" Season 1, Episode 1. This study is essential to be conducted because by knowing the use of address terms, people will learn how to address people adequately in communication. This research used a theory by Wardhaugh (2006) about addressing terms as the leading theory and by Braun as the supporting theory. For the method, the descriptive qualitative method was used. According to the findings of this study, there are three types of addressing terms and five social factors associated with the addressing terms found in the "Emily in Paris" Season 1 Episode 1 movie manuscript. The documentation and observation method were used to find the data. The three types of addressing terms were the use of a name, intimacy expression, and title with respect, where the most common address term is using the name. At the same time, five factors of addressing terms were Particular Occasion, Gender, Age, Occupational Hierarchy, and Degree of Intimacy.